Assessment of depression severity with the PHQ-9 in cancer patients and in the general population. Issue 1 (December 2016) - Hinz, Andreas; Mehnert, Anja; Kocalevent, Rüya-Daniela; Brähler, Elmar; Forkmann, Thomas; Singer, Susanne; Schulte, Thomas
Abstract Background The Patient Health Questionnaire PHQ-9 is a widely used instrument to screen for depression in clinical research. The first aim of this study was to psychometrically test the PHQ-9 in a large sample of cancer patients. The second aim was to calculate unbiased estimates of the depression burden for several cancer groups taking into account age and gender distributions. Methods A sample of 2, 059 cancer patients with varying diagnoses were examined in this study six months after discharge from a rehabilitation clinic. A representative sample of 2, 693 people from the general population served as controls. Expected PHQ-9 mean scores of the general population sample, regressed on age and gender, were calculated to enable a fair comparison of different groups of cancer patients. Results While the reliability (Cronbach's alpha) for the PHQ-9 scale was good (alpha ≥ 0.84), the CFA fit indices of the one-dimensional solution were unsatisfactory in the patients' sample. The factorial analysis confirmed two factors. PHQ-9 mean scores for 15 types of cancer are given, ranging from 4.0 (prostate) to 8.2 (thyroid gland). Differences between expected mean scores (derived from the general population) and raw mean scores of the cancer subsamples are reported that provide a better estimate of the depression burden. Conclusions The results confirmed that the PHQ-9 performs well in testing depression in cancer patients. Regression coefficients can be used for performing unbiased comparisons among cancer groups, not only for this study. The burden of patients with testis cancer and Hodgkin lymphoma is underestimated when age and gender are not taken into account.